Kepastian Hukum Status Tanah Ulayat Yang Dijadikan Hak Guna Usaha Setelah Habis Masa Berlakunya - Karani, Pasnelyza; Khairani, Khairani (Faculty of Law, Andalas University, 2025)
The According to the provisions of Article 28 paragraph (1) of the Basic Agrarian Law,